From animal hibernation to human’s hypometabolism: cellular mechanisms of natural and artificial hypobiosis - Repina, S.V.; Nardid, O.A.; Shylo, O.V.; Kovalenko, I.F. (Український антарктичний журнал, 2017)
Objective: to carry out a comparative study of structural and functional responses of rats and hamsters RBCs when the animals entered and left an artificial hypobiosis state under conditions of hypothermia-hypoxia-hypercapnia.